(untitled) (Applied Biological Research, 2013)
The length-weight relationships (LWR) of commercially important Indian major carp (Labeo rohita Ham. 1822) from three water bodies of southern Rajasthan viz., Mahi Bajaj Sagar (MBS), Surawania Dam (SD) and Aasana Pond (AP) were studied. The important parameters on LWR were calculated for Rohu in these selected water bodies and the correlation coefficient ‘r’ was significant with observed values of 0.99, 0.99 and 0.97 for MBS, SD and AP, respectively for pooled data. However, these values ranged from 0.74-0.88 in MBS, 0.46-0.95 in SD and 0.75-0.95 in AP in different length groups of Rohu. In LWR (W = aLb) values of exponent ‘b’ were observed to be 2.98, 2.97 and 3.14 in MBS, SD and AP in the pooled data. The values of ‘K’ ranged from 2.01-2.21 in MBS, 2.05-2.34 in SD and 2.05-2.29 in AP in different length groups. Such values for pooled data were 2.02, 2.05 and 2.38 for MBS, SD and AP fishes respectively which shows that comparatively AP is more conducive water body for the fish growth. The values of ‘Kn’ ranged from 0.99-1.00 which depicted condition of fish in these water bodies. These observed parameters were useful to evaluate the well being of Rohu population in the water bodies and provided useful information on fish biology for scientific management of fisheries.